Presence of Foodborne Pathogens in Seafood and Risk Ranking for Pathogens - Dümen, Emek; EKİCİ, GÖZDE; Ergin, Sevgi; Bayrakal, Gülay Merve (Mary Ann Liebert, Inc., 2020)
This study aims at examining the contamination of coliform bacteria, Escherichia coli, Listeria monocytogenes, Vibrio vulnificus, and Vibrio cholerae, which carry extremely serious risks to the consumer health, in 700 seafood belonging to 4 different (raw sea fish, raw mussels, raw shrimp, and raw squid) categories. The total number of samples was determined as 700. When the obtained results were viewed in total, they were found to be 48.14%, 18.71%, 8.57%, and 3.42% for coliform bacteria, E. coli, L. monocytogenes, and V. vulnificus, respectively. V. cholerae, one of the factors studied, was not found. Conventional microbiological cultivation methods were used in the analysis stage as well as the real-time PCR method. This study aims at making a risk ranking modeling for consumer health based on product category and pathogens by interpreting the results of the analysis with statistical methods. According to the statistical analysis, significantly binary correlations were determined among some parameters that stimulate one another for reproducing. In the light of the obtained results of the study, it has been concluded that the studies of the most detailed examinations of the microbiological risks associated with seafood, forms of microbial pollution and microorganisms that cause deterioration in seafood and threaten consumer health and the path that their epidemiologies follow, are of primary importance to both protecting consumer health and obtaining safe and quality seafood.
Keywords: Seafood; Food Pathogens; Food Safety; Risk Ranking